2007
DOI: 10.1038/sj.bjc.6604030
|View full text |Cite
|
Sign up to set email alerts
|

Weekly administration of docetaxel in combination with estramustine and celecoxib in patients with advanced hormone-refractory prostate cancer: final results from a phase II study

Abstract: The objective of this study was to evaluate the efficacy and safety profile of weekly docetaxel, estramustine and celecoxib in patients with advanced hormone-refractory prostate cancer. Forty-eight patients received 35 mg m À2 of weekly docetaxel for 3 out of every 4 weeks, 280 mg of estramustine twice daily on days 1 -3, 8 -10, 15 -17 and 400 mg of celecoxib twice daily until progression or toxicity. Cycles were repeated every 28 days for at least six cycles. Patients were evaluated for response and toxicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Selective inhibitors of COX-2 have been reported to reduce the formation, growth and metastasis of experimental tumors. Among the COX-2 inhibitors that show promise in cancer therapy is celecoxib, which shows marked efficacy against experimental tumors (6,7) and is currently the subject of ongoing clinical trials (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Selective inhibitors of COX-2 have been reported to reduce the formation, growth and metastasis of experimental tumors. Among the COX-2 inhibitors that show promise in cancer therapy is celecoxib, which shows marked efficacy against experimental tumors (6,7) and is currently the subject of ongoing clinical trials (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Several trials are testing the efficacy of drugs like Docetaxel, Celecoxib and others in combination that can bring down PSA levels, reduce pain and prolong the survival in patients with HRPC. 6 Previous reports in literature have demonstrated that selenium compounds are superior antitumor agents to their corresponding sulfur compounds. 34,35 In particular, seleniumenriched garlic was superior to regular garlic, 36 Se-methylselenocysteine was better than S-methylcysteine, 37 and diallyl selenide was better than diallyl sulfide 38 in mammary cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…8 A previous clinical trial using docetaxel in combination with Celecoxib has provided effective treatment for HRPC. 6 Additional reports indicate that the efficacy of chemotherapeutic agents such as doxorubicin, taxol and topoisomerase I inhibitor can be enhanced when used in combination with selenium to control experimental prostate cancer. 12,13 Although the combination regimen is a credible approach, we used an alternative and novel strategy by placing a selenium containing functionality in the backbone of the Celecoxib molecule itself, to generate a new class of compounds named Selenocoxibs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been evidence of modest biologic activity for celecoxib in men with rising PSA levels after radical prostatectomy and/or radiation therapy for prostate cancer. A recent study suggests that celecoxib with weekly docetaxel and estramustine is an effective and safe treatment for patients with hormone-refractory prostate cancer, but it does not seem to add any benefit to docetaxel [79].…”
Section: Cox-2 Inhibitors Induce Apoptosis Of Human Prostate Cancer Cmentioning
confidence: 99%